1999
DOI: 10.1021/jo9901440
|View full text |Cite
|
Sign up to set email alerts
|

Cation-Templated Self-Assembly of a Lipophilic Deoxyguanosine:  Solution Structure of a K+−dG8Octamer

Abstract: The lipophilic nucleoside 3‘,5‘-didecanoyl-2‘-deoxyguanosine, dG 1, extracts potassium salts from water into organic solvents. The K+ extraction drives the self-association of dG 1 to give G-quartet structures. A series of 1H NMR experiments indicates that the identity of the assembled species in CDCl3 is modulated by the amount of K+ extracted by dG 1. At an 8:1 dG 1 to K+ picrate ratio, the octamer (dG 1)8−K+ predominates in solution. The (dG 1)8−K+ supramolecular complex, formed by coordination of a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
112
0
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 99 publications
(121 citation statements)
references
References 45 publications
6
112
0
3
Order By: Relevance
“…[208] Depending on conditions, dG (17) [209] To better understand the transition from molecule to defined aggregate to ordered phase in organic solvents, we collaborated with Gottarelli et al to determine the NMR structure of the octamer [17] (17). [210] Remarkably, the NMR data indicated that this octamer was a single diastereomer. In one G-quartet, all dG units had a syn-glycosidic conformation, while the other tetramer had an "all-anti" conformation.…”
Section: Early Intermediates In Guanosine Self-assembly: Discrete G 8mentioning
confidence: 99%
“…[208] Depending on conditions, dG (17) [209] To better understand the transition from molecule to defined aggregate to ordered phase in organic solvents, we collaborated with Gottarelli et al to determine the NMR structure of the octamer [17] (17). [210] Remarkably, the NMR data indicated that this octamer was a single diastereomer. In one G-quartet, all dG units had a syn-glycosidic conformation, while the other tetramer had an "all-anti" conformation.…”
Section: Early Intermediates In Guanosine Self-assembly: Discrete G 8mentioning
confidence: 99%
“…This downfield resonance for N2-H A is characteristic of G-quartet formation where this proton is involved in the cyclic H-bonded scheme. [21] Because only one set of signals were observed, all the molecules must adopt the same conformation and the G-quartets must stack with a D 4 -symmetry (i.e., in a head-to-head or tail-to-tail manner). [22] As also observed by CD spectroscopy, the sequential addition of cryptand, acid, and base (Fig.…”
mentioning
confidence: 99%
“…Our and Davis groups collaborated to determine the structure of the octamer 2 8 ·K + in chloroform, the first detectable intermediate in the cation-directed self-assembly of 2, by NMR spectroscopy. [16] This octameric assembly is very robust and its stability is impressive for a non-covalent assembly. The H NMR spectra, essentially temperature independent over more than 100 8C, show two sets of signals in a 1:1 ratio corresponding each to nucleosides with different glycosydic conformation (syn-like and anti-like).…”
Section: Supramolecular Organisation Of Guanosine Derivativesmentioning
confidence: 98%